Polymer nanocomposites handbook (CRC Press, 2010)
Reflecting the exceptional growth in recent years in the use of nanostructured materials for an increasing range of industrial applications, Polymer Nanocomposites Handbook comprehensively covers the synthesis of both nanomaterials that act as the building blocks of polymer nanocomposites as well as polymers that act as matrix materials. It examines molecular precursors and related challenges for large-scale manufacturing. It describes current processing techniques and the difficulty to obtain good dispersion. Discussing future applications in civilian and defense-related fields, it also presents methods to characterize the bulk and interfacial structure of polymer nanocomposites.